Considering the Effect of Various Silica Types on Chemical, Physical and Mechanical Properties in Cement Mortar Production via Substitution with Cement Content - Osman Hansu (Buildings)
The main objective of this study is to reduce CO2 emissions resulting from rapidly increasing cement production and utilization rates worldwide. For this purpose, the effects of NS (nano-silica) and SF (silica fume) materials, which are the post-production wastes of industrial products, the substitute material obtained by grinding SG (silica gel) wastes used for packaging purposes in the preservation of industrial electronic products and many other areas, and MLS (micritic limestone) obtained by grinding limestone, a natural resource, on mortars after cement substitutions were evaluated. MLS and SG contents were sieved through a 0.063 mm sieve and substituted into the mixtures, while specific surface area values for SF and NS were obtained as 23 m2/g and 150 m2/g. Each of these materials was used in mortars by substituting between 0% and 10% cement by weight. The samples were subjected to consistency determination and then evaluated for setting time. Subsequently, flexural tests were carried out on 40 mm × 40 mm × 160 mm specimens placed in molds, and compressive tests were carried out on prism fragments broken after flexural tests. The experimental results showed that substitution of SG substitutes with cement at 3–10 wt% was highly effective against SF, NS and MLS in terms of strength and workability properties.